Dissenting Opinions in the 2024 Electoral Disputes and the Legitimacy of the Elected President and Vice President: Dissenting Opinion dalam Sengketa PHPU 2024 dan Legitimasi Presiden-Wakil Presiden Terpilih - Putra, Arsyi Manggali Arya; Rafiqi, Ilham Dwi (Lex Renaissance, 2025)
This study aims to examine the following problems: First, how does the dissenting opinion influence the 2024 General Election Results Dispute decision on the Legitimacy of the Elected President-Vice President? Second, What are the implications of the dissenting opinion on the 2024 General Election Results Dispute decision on the legitimacy of the President-Vice President's office? This study uses a normative legal research method with a statutory regulatory approach and a conceptual approach. The analysis technique is descriptive qualitative, interpretative, and heuristic. The study of this research is the Dissenting Opinion by three Constitutional Court Judges in Decision Number 1/PHPU.PRES-XXII/2024 and Number 2/PHPU.PRES-XXII/2024. The results of the study indicate the influence of dissenting opinion on the legitimacy of the elected President and Vice President, for a good democratic society, a desired national ideal. In addition, interpreting the dissenting opinion regarding the General Election Results Dispute (Pemilu) as a reference for improving future elections to be better. The dissenting opinion in this case provides a new perspective and interpretation of the election contestation in Indonesia. One of the most fundamental causes of the 2024 presidential and vice-presidential election was the incumbent's irregularities or interference in the election agenda. Furthermore, concerns were raised regarding the lack of neutrality of state civil servants, the distribution of social assistance funds leading up to the election and during the campaign period, and political ethics. Consequently, an imbalance occurred in the presidential and vice-presidential nomination process, creating new problems in resolving the 2024 election dispute.